OPINIONS ABOUT THE INFLUENCE OF PRELIMINAL CORONARY REVASCULARIZATION ON THE PREVALENCE OF CARDIAL COMPLICATIONS IN NONCARDIAC SURGERY - E. A. Surkova; Yu. V. Shchukin (Российский кардиологический журнал)
Prognosis and prevention of cardiac complications of non-cardiac surgery is an important clinical task. Currently quite a lot is known on various scales of myocardial infarction risk prognosis and the death in perioperational period, as on drug treatment and prevention. The issue whether to perform coronary arteriography and preventive coronary revascularization before noncardiac surgical interventions in patients with high cardiological risk score remains controversial. Current review concerns on the perspectives of perioperational myocardial infarction pathogenesis and also analyses in details the results of current retro- and prospective studies of efficacy and safety of various types of preventive coronary revascularization with the aim to reduce the prevalence of extracardiac surgery.